Introduction to Difference Equations: With Illustrative Examples From Economics, Psychology, and Sociology - Goldberg, Samuel (New York: Wiley, 1958)
This book is primarily intended for social scientists who wish to understand the basic ideas and techniques involved in setting up and solving difference equations. The mathematical topics in the text are related to and illustrated by material drawn from the social sciences, especially economics, psychology, and sociology.
Includes bibliography.
ne 01/03/2018
Loans
Keywords: Difference Equations; Social Sciences